2009
DOI: 10.1109/twc.2009.080882
|View full text |Cite
|
Sign up to set email alerts
|

On analytical derivations of the condition number distributions of dual non-central Wishart matrices

Abstract: Abstract-In this paper, we explore the statistical characterization of Multiple-Input Multiple-Output (MIMO) channel correlation matrices with the main focus being on their condition number statistics. More specifically, novel expressions are derived for the probability density function (PDF) and cumulative distribution function (CDF) of the MIMO condition number. Contrary to the majority of related studies, where only the common case of Rayleigh fading was considered, our investigation is extended to account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The SCN analysis of [41] was extended in [47] to allow for matrices of arbitrary size and arbitrary correlation structures; however, the final result for the SCN PDF was given as a complicated expression involving an infinite series of zonal polynomials, and is thus difficult to manage. Finally, the exact SCN distributions for dual complex non-central Wishart matrices with two DoF were recently presented in [48].…”
Section: Introductionmentioning
confidence: 99%
“…The SCN analysis of [41] was extended in [47] to allow for matrices of arbitrary size and arbitrary correlation structures; however, the final result for the SCN PDF was given as a complicated expression involving an infinite series of zonal polynomials, and is thus difficult to manage. Finally, the exact SCN distributions for dual complex non-central Wishart matrices with two DoF were recently presented in [48].…”
Section: Introductionmentioning
confidence: 99%
“…In [17], we found that when κ ≤ 6.46 the instantaneous capacity of the HR channel is greater than the ergodic capacity of a common (2×2) i.i.d. Rayleigh channel and hence we have adopted a threshold of κ = 5 as a reasonable indicator of the channel rank and multipath richness.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In such a case though, the (λ 1 − λ 2 ) term in the denominator of (2) becomes zero making the analysis invalid (division by zero). In this light, we consider a suboptimum HR LoS channel model in order to guarantee that λ 1 = λ 2 ; the LoS matrix component then reads [17] …”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Wishart matrix theory [15]- [18], numerous channel models have been proposed in the literature for MIMO communication systems [19]- [26]. A closed-form joint probability density function (PDF) of eigenvalues of Wishart matrix was derived for evaluating the performance of MIMO communication systems [19].…”
mentioning
confidence: 99%